A candidate multi-epitope vaccine against porcine reproductive and respiratory syndrome virus and Mycoplasma hyopneumoniae induces robust humoral and cellular response in mice. Issue 16 (6th April 2022) - Gao, Zhisong; Chen, Lingxiao; Song, Tao; Pan, Xuan; Li, Xiaojing; Lu, Guangzong; Tang, Yajie; Wu, Xiang; Zhao, Baohua; Zhang, Ran
Highlights: Recombinant epitope protein rEP-PM contains some B cell epitopes and T cell epitopes of PRRSV-GP5, PRRSV-M, Mhp-P46 and Mhp-P65 protein. rEP-PM could induce the production of high levels of antibodies. rEP-PM could induce the Th1-dominant cellular immune response in mice. rEP-PM has good immunoreactivity with anti-rEP-PM, anti-PRRSV and anti-Mhp antibodies. Anti-rEP-PM antibody could specifically recognize proteins from PRRSV and Mhp. Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) and Mycoplasma hyopneumoniae ( M. hyopneumoniae, Mhp) are two of the most common pathogens involved in the porcine respiratory disease complex (PRDC) resulting in significant economic losses worldwide. Vaccination is the most effective approach to disease prevention. Since PRRSV and Mhp co-infections are very common, an efficient dual vaccine against these pathogens is required for the global swine industry. Compared with traditional vaccines, multi-epitope vaccines have several advantages, they are comparatively easy to produce and construct, are chemically stable, and do not have an infectious potential. In this study, to develop a safe and effective vaccine, B cell and T cell epitopes of PRRSV-GP5, PRRSV-M, Mhp-P46, and Mhp-P65 protein had been screened to construct a recombinant epitope protein rEP-PM that has good hydrophilicity, strong antigenicity, and high surface accessibility, and each epitope is independent and complete. After immunization in mice, rEP-PM could induce the production of high levels of antibodies, and it had good immunoreactivity with anti-rEP-PM, anti-PRRSV, and anti-Mhp antibodies. The anti-rEP-PM antibody specifically recognizes proteins from PRRSV and Mhp. Moreover, rEP-PM induced a Th1-dominant cellular immune response in mice. Our results showed that the rEP-PM protein could be a potential candidate for the development of a safe and effective multi-epitope peptide combined vaccine to control PRRSV and Mhp infections.